UNPROVOKED UPPER EXTREMITY DEEP VEIN THROMBOSIS IN PATIENT WITH PRIMARY ANTIPHOSPHOLIPID SYNDROME: A CASE REPORT - Hermifa Dwi Aninnaimah; Awalia (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Upper extremity deep vein thrombosis is less common than in the lower extremity site. Such conditions can appear primarily or secondary to other conditions such as thrombophilia. One of the unique forms of acquired autoimmune thrombophilia is antiphospholipid syndrome (APS). We describe a 25 years old female admitted with sudden swelling, redness, and pain in her left arm. Venous ultrasound confirmed the diagnosis of thrombosis in the left subclavian vein, left axillary vein, left proximal brachial vein, and left proximal basilic vein. The patient was known to have a spontaneous miscarriage in the second pregnancy at eight weeks of gestation. Screening for autoimmune and antibody phospholipid was done, and primary APS was confirmed. She has been treated with a subcutaneous injection of fondaparinux 2.5 mg for five days and oral rivaroxaban 15 mg twice daily for 21 days. But four months later, the patient came with a thrombus in the subclavian vein due to inadequate treatment, then long-term treatment with vitamin K antagonist warfarin proceeded.